(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
In the current age of digitalization, cyber deception has become increasingly pervasive, posing significant threats to individuals and assets. As malicious actors exploit network vulnerabilities, developing adaptable defense strategies has become imperative. This research study aims to gain insights into consumer experiences with cyber scams and their emotional resilience. The findings from this study will be valuable to Bestlink College of the Philippines, specifically its Psychology department, in addressing cyber threats and ensuring data protection. This study investigates the impact of cyber-deception experiences on faculty members’ emotional resilience, exploring how these experiences shape emotional responses. This study employs a Descriptive Correlational Research Design and a quantitative approach. A 5-point Likert scale questionnaire and standardized tests are utilized. The researcher purposively selected fifty (50) faculty members from Bestlink College of the Philippines. The study examined how individuals perceived and experienced cyber-deception, particularly in scenarios such as automatic money transfers, social media hacking, and linking to illegal websites. The findings showed that respondents generally had neutral attitudes toward these experiences, although there was agreement on the issue of accessing illegal websites. However, when analyzing the relationship between cyber-deception and emotional resilience, the study found only a weak positive correlation. This suggests that while there may be some connection between experiencing cyber-deception and emotional resilience, it is not particularly strong. Therefore, the impact of cyber-deception on emotional resilience may vary among individuals. Despite the prevalence of cyber-deception incidents, individuals often maintain a neutral attitude toward such experiences, suggesting a potential lack of awareness or perception of these incidents as significant threats in their daily lives. This observation underscores the need for further research to examine the correlation between cyber-deception encounters and emotional resilience. Additionally, raising public awareness of cyber threats and equipping individuals with the necessary skills to safeguard themselves in the digital age are of paramount importance. The study’s findings highlight the need to better understand and address the complexities of cyber-deception to enhance overall digital safety and resilience.